Agroclimatic classification for assessment Of the crop potential of Karnataka - KHAMBETE, N.N. (MAUSAM, 1992)
To plan cropping pattern and to bring out agricultural potential of a region, it is essential that the agro climatic classification is made on an objective and rational basis. Such an attempt has been made in this paper by devising an index called Water Availability Index (WAI). This index takes into account the distribution of the minimum water required by the crop. It utilizes the most probable number of the wet weeks for three threshold values of weekly rainfall and probability of dry spells of more than three weeks. The methodology developed is applied to dry farming tracts of Karnataka State. Using these information along with the information of the soil types and water requirement of different crops, cropping pattern can be assessed in each agro climatic zone, so that optimum use of the available moisture is made in stabilizing the crop production in the State.